ТАРИЙХЫЙ ҚОСЫҚЛАРДА ТАРИЙХЫЙ ҲАҚЫЙҚАТЛЫҚ (Тарийхый қосықларда Хорезм журты темасы мысалында) - Қанаатов, Е.Е. (SCIENCE and SOCIETY, 2020)
The article provides information about the Karakalpaks who migrated from Khorezm to Baysun, which was destroyed in the first quarter of the 13th century due to the invasion of Genghis Khan’s troops. In the history of this period there is little information about the life of the Karakalpaks. However, folklore works, including historical songs preserved in the mouths of the people, serve as a much richer historical source in this regard. The song “Baysinga” was created almost 800 years ago. In 1221, Genghis Khan conquered Gurganj (Urgench), the capital of the Khorezm state, and flooded the great city. The irrigation system in the area was disrupted, and people were forced to move. Despite the fact that many years have passed, the song is well preserved to this day.